2015
DOI: 10.1371/journal.pone.0144395
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Visual Integration in Children with Traumatic Brain Injury: An Observational Study

Abstract: BackgroundAxonal injury after traumatic brain injury (TBI) may cause impaired sensory integration. We aim to determine the effects of childhood TBI on visual integration in relation to general neurocognitive functioning.MethodsWe compared children aged 6–13 diagnosed with TBI (n = 103; M = 1.7 years post-injury) to children with traumatic control (TC) injury (n = 44). Three TBI severity groups were distinguished: mild TBI without risk factors for complicated TBI (mildRF- TBI, n = 22), mild TBI with ≥1 risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…general neurocognitive functioning, attention and visual integration) and behavior problems (i.e. internalizing and externalizing problems; Königs et al 2015a , b ). Together, these findings call for careful clinical screening for adverse neurocognitive and behavioral outcome in children with mild RF+ TBI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…general neurocognitive functioning, attention and visual integration) and behavior problems (i.e. internalizing and externalizing problems; Königs et al 2015a , b ). Together, these findings call for careful clinical screening for adverse neurocognitive and behavioral outcome in children with mild RF+ TBI.…”
Section: Discussionmentioning
confidence: 99%
“…mild RF+ ; e.g. skull fracture, persistent vomiting, focal neurological impairment) are at risk of poor neurocognitive and behavioral outcome (Königs et al 2015a , b ). Importantly, functional outcome of mild to severe TBI is characterized by a distinct inter-individual heterogeneity that remains poorly understood (Polinder et al 2015 ), and therefore complicates reliable prognosis of neurocognitive and behavioral outcome.…”
Section: Introductionmentioning
confidence: 99%
“…When SWI is used concurrently with DTI, adequate detection of acute hemorrhage and diffuse axonal injury can be obtained [105]. Axonal injury can contribute to impaired sensory integration, which can be detected through visual and auditory exams [106]. Not surprisingly, Galvin and colleagues reported that the majority of children score outside the range of typical sensory processing when administered a sensory profile following TBI [92].…”
Section: Advanced Imaging Correlationsmentioning
confidence: 99%
“…The diffusion model (Ratcliff, 1978) is an extensively studied computational model that allows researchers to dissect task performance into the separate contributions of task strategy (i.e., boundary separation, describing individual speed-accuracy trade-off settings), efficiency of information processing (i.e., drift rate) and extradecisional processes (i.e., nonde-cision time, involving stimulus encoding, as well as preparation and execution of the motor response). Recently, we have successfully applied the diffusion model to a paradigm measuring the integration of visual information (Königs, Weeda, et al, 2015). A detailed description of the diffusion model and its validation is beyond the scope of current study, but is provided elsewhere (Ratcliff et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, the literature on the specific effects of TBI on multisensory integration in children with TBI is scant. In previous work, we have studied the effects of pediatric TBI on the integration of information within the visual modality (i.e., visual integration of stimulus identity and location), revealing reduced visual integration efficiency in children with mild TBI and risk factors for complicated TBI, and in children with moderate/severe TBI (Königs, Weeda, et al, 2015). Given the diffuse effects of TBI on structural brain connectivity (Sharp et al, 2014), we argue that the observed integration deficits in children with TBI may not be limited to the visual domain.…”
mentioning
confidence: 99%